2008
DOI: 10.1111/j.1749-124x.2008.00114.x
|View full text |Cite
|
Sign up to set email alerts
|

Has Minority Foreign Investment in China's Banks Improved Their Cost Efficiency?

Abstract: Since 2001, foreign investors have been permitted to acquire minority ownership stakes in China's banks. This paper assesses whether there is any evidence of a cost efficiency payoff in those banks that have taken on foreign investment. Data envelopment analysis is first used to generate measures of cost efficiency for China's banks over the period 2001-2006. A second stage regression is then performed to determine whether foreign investment has an impact on cost efficiency. The results indicate a positive rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 17 publications
(24 reference statements)
6
22
0
1
Order By: Relevance
“…By enhancing the efficiency of capital market infrastructure, China has made great efforts towards changing its accounting regulations (Chen, Wang and Zhao, 2009). With the ongoing liberalisation of the Chinese economy and the increasingly competitive business environment, the need for Chinese firms to ensure greater efficiency and improve the quality of their financial reporting have become understandably very high (Laurenceson and Qin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…By enhancing the efficiency of capital market infrastructure, China has made great efforts towards changing its accounting regulations (Chen, Wang and Zhao, 2009). With the ongoing liberalisation of the Chinese economy and the increasingly competitive business environment, the need for Chinese firms to ensure greater efficiency and improve the quality of their financial reporting have become understandably very high (Laurenceson and Qin, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Foreign financial institutions have much higher incentives for technology transfer if they hold large equity shares of Chinese banks. However, low equity stake potentially provides insufficient incentives to transfer technologies to Chinese banks, because foreign investors can receive only a small part of the increased value (Laurenceson & Qin, 2008). Foreign financial institutions have large equity stake in CCBs, RCBs and most JOCBs than that of SOCBs, so they have more incentive to transfer technologies to CCBs, RCBs and most JOCBs.…”
Section: Proposition 2:more Directors Sent By Foreign Financial Instimentioning
confidence: 99%
“…Moreover, Berger et al (2009) analyzed the efficiency of 38 Chinese banksover [1994][1995][1996][1997][1998][1999][2000][2001][2002][2003], and found that minority foreign ownership is associated with significantly improved efficiency and minority foreign ownership of the Big Four will likely improve performance significantly.However, Shen et al (2009) Berger et al (2009) found positive and significant impact of foreign bank entry. Shen et al (2009), Laurenceson andQin (2008), and Yuan and Gunji (2009) found no impact or small impact of the foreign entry. One main reason for the inconsistent results is that they don't consider the variety of Chinese banks which is strategically invested by foreign financial institutions.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies had also explored the relationship between the efficiency of the banks, profitability, risks and ownership structure (Yao et al, 2004;Zhang, 2003;Qian, 2003;Zheng and Cao, 2005;Wang and Tan, 2007;Laurencenson and Qin, 2008). Banks that were more profitable, with higher ROA and ROE, appeared to be more efficient, whereas banks with poor cost control, with higher ratios of cost-to-income or total cost to total assets, were less efficient (Yao et al, 2004).…”
Section: Efficiency Studies Of the Chinese Banking Sectormentioning
confidence: 99%